The Effect of Leadership on Performance Employee at PT Cipta Manunggal Sukses Bogor - Furi Indriyani; Annisa Nur Fitria; Ida Hendarsih; Tati Mardewi (INTERACTION: Jurnal Pendidikan Bahasa, 2023)
An organization can achieve its goals if it is supported by competent human resources and experts in their fields. To get these competent human resources, good performance is needed from all employees. Various factors are needed so that employees can provide maximum results at work, one of which is leadership. This study aims to determine how much leadership influences employee performance at PT Cipta Manunggal Sukses Bogor. The research method used was descriptive quantitative by distributing questionnaires to 40 respondents and analyzing the data using SPSS 25. From the results of this study, leadership has a fairly good influence on employee performance which can be seen from the correlation test of 0.799, which states that the correlation between leadership and employee performance is quite high. The results of the determination test showed the number 0.638, or it can be interpreted that leadership affects 63.8% of employee performance. The results of the regression equation test obtained a significant value of 0.00<0.005 with the equation Y = 12.904 + 0.602x, which means that the leadership brought is good in its role so that employee performance increases.